Efficacy of rehabilitation robotics for walking training in neurological disorders: A review - Tefertiller, Candace; Pharo, Beth; Evans, Nicholas; Winchester, Patricia (Journal of rehabilitation research and development, 2011)
Robotic technologies are becoming more prevalent for treating neurological conditions in clinical settings. We conducted a literature search of original articles to identify all studies that examined the use of robotic devices for restoring walking function in adults with neurological disorders. We evaluated and rated each study using either the Physiotherapy Evidence Database scale for randomized controlled trials (RCTs) or the Downs and Black scale for non-RCTs. We reviewed 30 articles (14 RCTs, 16 non-RCTs) that examined the effects of locomotor training with robotic assistance in patients following stroke, spinal cord injury (SCI), multiple sclerosis (MS), traumatic brain injury (TBI), and Parkinson disease (PD). This review supports that locomotor training with robotic assistance is beneficial for improving walking function in individuals following a stroke and SCI. Gait speed and endurance were not found to be significantly different among patients with motor incomplete SCI after a variety of locomotor training approaches. Limited evidence demonstrates that locomotor training with robotic assistance is beneficial in populations of patients with MS, TBI, or PD. We discuss clinical implications and decision making in the area of gait rehabilitation for neurological dysfunction.